Exploring institutional governance dynamics in China’s transnational higher education (TNHE): a study of Sino-foreign joint institutes - Huili Si; Stephen Rayner (Cogent Education)
As China emerges as a prominent destination for international higher education, universities globally are forming partnerships with Chinese institutions. This article examines governance dynamics by assessing the influence of stakeholders who work between Chinese and international partner universities, with a particular focus on Sino-foreign joint institutes. Semi-structured interviews were conducted with 16 such stakeholders to explore their perceptions of institutional governance. Grounded in organizational theory, the article applies Verhoest et al.’s (2004) governance typology and the indicators by De Boer and Enders (2017) to provide conceptual and empirical insights into Transnational Higher Education (TNHE) governance in China. The findings indicate increased autonomy for individual institutions in terms of governance. China’s Deanship and Joint Committee operations in Sino-foreign joint institutes, while continuing to integrate top-down decision-making, are incorporating transnational actors as the joint partners in governance and leadership, most notably in financial and structural governance. We also propose that resolving tensions for sustainable partnerships requires Chinese stakeholders to implement harmonious governance in TNHE partnerships, while international stakeholders should embrace adaptive governance.